A step towards sustainable development in higher education in India by implementing new media technologies: A paperless approach. Issue 2 (12th February 2019) - Jampala, Maheshchandra Babu; Shivnani, Tina
Abstract : Purpose: The purpose of this paper is to focus on changing the dynamics of higher education in the Indian education system toward a paperless approach by implementing new media technologies. Design/methodology/approach: The review paper highlights the need for sustainable development in higher education by using new media technologies by providing them with some real-time examples used in universities. This paper also highlights a different step toward the paperless approach in various universities in India. This paper draws the analysis based on the recent review of the literature as well as experience at the professional level. Findings: The author discusses how the implementation of different new media technologies is helping universities in shifting toward a paperless approach for sustainable development and concern toward the environmental threat. To support the evidence, the authors have given some real-time examples through data collection and observations of various uses of new media technologies among private universities. Originality/value: This paper provides an overview of various new media technologies and blends the critical issues of how technologies are changing the educational dimension toward a paperless approach among public and private universities in India. The paper also proposes to create a sustainable model by addressing the challenges by which the universities can support themselves and others.